Ubiquitin Proteasome System Current Insights into Mechanism Cellular Regulation and Disease - Summers, Matthew (IntechOpen, 2019)
The human ubiquitin proteasome system (UPS) is comprised of nearly 1000 proteins. Although originally identified as a mechanism of protein destruction, the UPS has numerous additional functions and mediates central signaling events in myriad processes involved in both cellular and organismal health and homeostasis. Numerous pathways within the UPS are implicated in disease, ranging from cancer to neurodegenerative diseases such as Parkinson's. The goal of this book is to deliver a collection of synopses of current areas of UPS research that highlights the importance of understanding the biology of the UPS to identify disease-relevant pathways, and the need to elucidate the molecular machinations within the UPS to develop methods for therapeutic modulation of these pathways.